1985
DOI: 10.1051/jphyslet:01985004608039500
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer bending elasticity measured by Fourier analysis of thermally excited surface undulations of flaccid vesicles

Abstract: 2014 Nous mesurons l'élasticité de flexion de vésicules flasques par l'analyse de Fourier des ondulations thermiques de surface, jusqu'au 8e ordre. Les résultats sont expliqués par la théorie récente de Schneider et al. La constante élastique de flexion pour une bicouche fluide de lécithine (Kc = 4 x 10-13 erg) est en bon accord avec celle des membranes d'érythrocytes, mais est presque d'un ordre de grandeur plus faible que celle donnée pour les mêmes lipides dans la littérature. Ce désaccord est attribué au f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
1
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(97 citation statements)
references
References 10 publications
(21 reference statements)
5
90
1
1
Order By: Relevance
“…The bending modulus calculated ((0.21±0.08) × 10 −19 J) from force plots is in the same magnitude range (10 −20 to 10 −19 J) of literature reported value for the same EggPC lipid [9][10][11][12][47][48][49][50] (see Table 2) regardless of different geometry and size of the samples. Variations in bending modulus measured have been reported and the reason for the discrepancy still needs further analysis [49][50][51].…”
Section: Data Analysis According To Hertz Modelsupporting
confidence: 78%
See 1 more Smart Citation
“…The bending modulus calculated ((0.21±0.08) × 10 −19 J) from force plots is in the same magnitude range (10 −20 to 10 −19 J) of literature reported value for the same EggPC lipid [9][10][11][12][47][48][49][50] (see Table 2) regardless of different geometry and size of the samples. Variations in bending modulus measured have been reported and the reason for the discrepancy still needs further analysis [49][50][51].…”
Section: Data Analysis According To Hertz Modelsupporting
confidence: 78%
“…Several possibilities are proposed to explain the variations of bending modulus observed: (1) different experimental method: Niggemann et al [51] found that the values of the rigidity for the same lipid differed significantly between methods. Our data was derived from Young's modulus based on AFM force curves and others use phase contrast microscopy [9][10][11]47,48], magnetic-field [12], and electric field method [49,50]; (2) bending modulus (Eq. (2)) is based on three-dimensional, isotropic planar surface assumptions, while the vesicles on substrate is not prefect isotropic planar surface; (3) our data is based on the result on the adsorbed small size vesicles while other methods deal with giant liposomes (>10 m) vesicles.…”
Section: Data Analysis According To Hertz Modelmentioning
confidence: 99%
“…The bending rigidity of amphiphilic bilayers has been measured in many experiments: while phospholipid membranes [4,8,[20][21][22] are characterized by a bending rigidity of the order of tens of k B T , lamellar and fluid microemulsion phases composed of single chain surfactants, short chain alcohols, oil and water [23][24][25][26] exhibit a bending rigidity of the order of k B T . The bilayer studied in our Molecular Dynamics simulations are composed of single-chain amphiphiles and have bending rigidities which are of the same order of magnitude as those studied in the second group of experiments.…”
mentioning
confidence: 99%
“…We also predict an observable tension jump for membranes decorated with polymer "brushes". [6,7,8]. Here, σ is an effective surface tension, i.e., an adjustable thermodynamic parameter arising from the constraint of constant surface area, which is usually several orders of magnitude smaller than the surface tensions of ordinary liquid interfaces [9,10].…”
mentioning
confidence: 99%